Ochrona środowiska w ramach reform wspólnej polityki rolnej Unii Europejskiej na przełomie dwudziestego i dwudziestego pierwszego wieku - Kociszewski, Karol (Environment protection within the reform of European Union common agriculture policy at the turn of the twentieth and twenty first centuries, 2007)
The paper presents the most important environmental measures in the light of the reforms of Common Agriculture Policy which were introduced in the nineties of the twentieth century and in the first decade of the twenty first century. It refers to reforms from 1999 and 2003. The connections between agricultural and ecological policies were pointed out in the eontext of the European Union Strategy of Sustainable Development. Owing to their consideration, the changes which are currently being introduced could be a factor stimulating sustainable development. In the first place it relates to the growing significance of Common Agriculture II pillar - rural development programmes, including agri-environmental measures. Unfortunately, the way in which the agricultural policy is carried out in Poland is not compatible enough to the direction of Common Agriculture Policy evolution. The most important instruments are led in insufficiently and in a smali scale.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 394-403